2019
DOI: 10.2174/1389201020666190809110511
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan/Alginate-ellagic Acid Sustained-release Microspheres and their Inhibition of Preadipocyte Adipogenic Differentiation

Abstract: Objective: In this study, chitosan/alginate-ellagic acid sustained-release microspheres were prepared, and the effect of sustained-release microspheres on preadipocyte adipogenic differentiation was analyzed. Methods: Chitosan/alginate-ellagic acid microspheres were prepared and identified by scanning electron microscopy (SEM) and infrared spectroscopy (IR). The drug release rates were measured at pH 6.8, 7.0, 7.2, 7.4 to determine sustained release of ellagic acid from microspheres. The effects of 0.1, 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…A recent study by Ding et al focused on the preparation of EA microspheres based on CS and sodium alginate as coating materials [78]. CS-alginate microparticles (MPs) were prepared by ionotropic gelation.…”
Section: Chitosan Micro/nanospheresmentioning
confidence: 99%
“…A recent study by Ding et al focused on the preparation of EA microspheres based on CS and sodium alginate as coating materials [78]. CS-alginate microparticles (MPs) were prepared by ionotropic gelation.…”
Section: Chitosan Micro/nanospheresmentioning
confidence: 99%
“…The obtained materials showed antioxidant activity [120]. Additionally, ellagic acid was used as a chitosan/sodium alginate modifier [146]. It was also added to a starch-based film as an active compound [147].…”
Section: Phenolic Acids With Other Natural Polymersmentioning
confidence: 99%
“…Growing evidence demonstrates that this strategy allows the delivery of higher local concentrations of drugs, which can enhance their therapeutic efficacy 73,74 . In this sense, novel drug-delivery systems that overcome the low EA solubility and bioavailability (i.e., biocompatible polymers-based nanoparticles/ microcapsules/ biofilms/ micelles) are being tested in vitro and in vivo [75][76][77][78][79] . In summary, we found that EA affects cell cycle progression of endometrial stromal cells through the arrest at G2/M phase.…”
Section: Discussionmentioning
confidence: 99%